Computational screening of 645 antiviral peptides against the receptor-binding domain of the spike protein in SARS-CoV-2. (September 2021) - Sakib, Md Minhas Hossain; Nishat, Aktiya Anjum; Islam, Mohammad Tarequl; Raihan Uddin, Mohammad Abu; Iqbal, Md Shahriar; Bin Hossen, Farhan Fuad; Ahmed, Mohammad Imran; Bashir, Md Samiul; Hossain, Takbir; Tohura, Umma Sumia; Saif, Saiful Islam; Jui, Nabilah Rahman; et al.
Abstract: The receptor-binding domain (RBD) of SARS-CoV-2 spike (S) protein plays a vital role in binding and internalization through the alpha-helix (AH) of human angiotensin-converting enzyme 2 (hACE2). Thus, it is a potential target for designing and developing antiviral agents. Inhibition of RBD activity of the S protein may be achieved by blocking RBD interaction with hACE2. In this context, inhibitors with large contact surface area are preferable as they can form a potentially stable complex with RBD of S protein and would not allow RBD to come in contact with hACE2. Peptides represent excellent features as potential anti-RBD agents due to better efficacy, safety, and tolerability in humans compared to that of small molecules. The present study has selected 645 antiviral peptides known to inhibit various viruses and computationally screened them against the RBD of SARS-CoV-2 S protein. In primary screening, 27 out of 645 peptides exhibited higher affinity for the RBD of S protein compared to that of AH of the hACE2 receptor. Subsequently, AVP1795 appeared as the most promising candidate that could inhibit hACE2 recognition by SARS-CoV 2 as was predicted by the molecular dynamics simulation. The critical residues in RBD found for protein-peptide interactions are TYR 489, GLY 485, TYR 505, and GLU 484. Peptide-protein interactions were substantially influenced by hydrogen bonding and hydrophobic interactions. This comprehensive computational screening may provide a guideline to design the most effective peptides targeting the spike protein, which could be studied further in vitro and in vivo for assessing their anti-SARS CoV-2 activity. Graphical abstract: Image 1 Highlights: Antiviral peptides can be a promising therapeutic strategy to inhibit SARS-CoV-2. 645 antiviral peptides were screened against RBD of the spike protein of SARS-CoV-2. 150 ns molecular dynamics simulation has been performed for peptide-protein complexes. Two promising peptides were found which show significant binding and interactions with RBD of SARS CoV-2.